Standardization Of Gomutra Haritaki Vati: An Ayurvedic Formulation - PRASAD V. KADAM; KAVITA N. YADAV; RAKESH S. SHIVATARE; ASHISH S. PANDE; ANKITA N. PATEL; MANOHAR J. PATIL (International Journal of Pharma and Bio Sciences, 2012)
Newer guidelines, for standardization, manufacturing, quality control and scientifically rigorous research will be necessary for traditional system. Gomutra haritaki is an ayurvedic formulation prescribed for the mouth disease. Information on the qualitative and quantitative parameters of Gomutra haritaki to guarantee the quality and the safety of the product to the consumer is less; many of these parameters were vary according to the method of preparations. With this aim in the recent study an attempt has been made to develop standardization methods of Gomutra haritaki vati. A comparative study has been made between in-house preparation and the two marketed formulation. These all formulations were standardized for various qualitative and quantitative parameters according to WHO guidelines. The set parameters were found to be sufficient to evaluate the vati and can be used as reference standards for the said formulation which will be part of the quality assurance for these formulations.